Determination of the number of free-living ticks in the semi-arid region of Paraíba, Caatinga Biome, Northeastern Brazil (Research, Society and Development, 2023)
Ticks are vectors that have a cosmopolitan distribution and wide diversity of hosts, transmitted diseases are one of the main public health problems in Brazil and in the world. Objective: to determine the prevalence of free-living ticks in the semi-arid region of Paraíba, Northeastern Brazil. Material and method: Ticks were collected weekly, from June to December 2019 through visual inspection and white flannel dragging. Result: In total, 5,235 ticks were collected. In area 1, 530 males, 274 females of which 64 were engorged, 280 nymphs and 382 larvae. In area 2, 1603 males, 2080 females of which 1007 were engorged and 86 nymphs. All specimens collected were of the species Riphicephalus sanguineus. The months with the highest number of ticks collected were October and November, in the two studied areas. The collection methods showed statistical difference (P < 0.001) regarding the number of ticks collected during the six-month period. The nymph and female stages of area 1 showed a positive correlation with maximum and minimum temperature. Conclusion: R. sanguineus was the only ixodid species found in the studied areas. The different characteristics of the collection areas demonstrate the ability of this species to maintain itself in each generation, giving continuity to its biological cycle. Additional studies of correlation between environment, parasite and host are extremely important to obtain data on the dynamics of infestation and transmission of hemoparasites transmitted by these ticks.